Cardiovascular Magnetic Resonance Relaxometry Predicts Regional Functional Outcome After Experimental Myocardial Infarction. (August 2017) - Haberkorn, Sebastian M.; Jacoby, Christoph; Ding, Zhaoping; Keul, Petra; Bönner, Florian; Polzin, Amin; Levkau, Bodo; Schrader, Jürgen; Kelm, Malte; Flögel, Ulrich
Abstract : Background—: Cardiovascular magnetic resonance with gadolinium-based contrast agents has established as gold standard for tissue characterization after myocardial infarction (MI). Beyond accurate diagnosis, the value of cardiovascular magnetic resonance to predict the outcome after MI has yet to be substantiated. Methods and Results—: Recent cardiovascular magnetic resonance approaches were systematically compared for quantification of tissue injury and functional impairment after MI using murine models with permanent left anterior descending coronary artery ligation (n=14) or 50 minutes ischemia/reperfusion (n=13). Cardiovascular magnetic resonance included native/postcontrast T1 maps, T2 maps, and late gadolinium enhancement at days 1 and 21 post-MI. For regional correlation of parametric and functional measures, the left ventricle was analyzed over 200 sectors. For T1 mapping, we used retrospective triggering with variable flip angle analysis. Sectoral analysis of native T1 maps already revealed in the acute phase after MI substantial discrepancies in myocardial tissue texture between the 2 MI models (native T1 day 1: permanent ligation, 1280.0±162.6 ms; ischemia/reperfusion, 1115.0±140.5 ms; P <0.001; n=14/13), which were later associated with differential functional outcome (left ventricular ejection fraction day 21: permanent ligation, 24.5±7.0%; ischemia/reperfusion, 33.7±11.6%; P <0.05; n=14/13). At this early time, any other parameter was indicative for the subsequent worsening of left ventricular ejection fraction in permanent ligation mice. Linear regression of acute individual measures with contractile function in corresponding areas at day 21 demonstrated for early native T1 values the best correlation with the later functional impairment ( R 2 =0.94). Conclusions—: The present T1 mapping approach permits accurate characterization of local tissue injury and holds the potential for sensitive and graduated prognosis of the functional outcome after MI without gadolinium-based contrast agents. Abstract : Supplemental Digital Content is available in the text.